Integrating Sustainability into Maritime Vocational Education: Focus on Marine Engineering for Naval Electrical Cadets - Pargaulan Dwikora Simanjuntak; Guntoro, R.Herlan (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2025)
This research explores the challenges faced by maritime vocational lecturers who balance studies with teaching responsibilities, specifically focusing on the integration of sustainability principles within maritime education, with a particular emphasis on transportation management. The study examines how lecturers, drawing from both academic research and practical teaching experience, incorporate sustainability practices such as green shipping and port decarbonization into curricula aimed at preparing students for the evolving demands of the maritime industry. Through qualitative interviews with maritime professionals, lecturers, and graduates, the research identifies critical factors for effective sustainability integration, including institutional support, time management, and faculty collaboration. The findings indicate that when lecturers are supported with adequate resources and flexibility, they can successfully balance dual roles and embed sustainability within their teaching practices. Furthermore, collaboration among faculty members emerged as a key strategy for enhancing the delivery of sustainability in transportation management curricula. The research highlights the need for institutions to adapt curricula and offer better support to lecturers, ensuring that graduates are well-prepared to meet the sustainability challenges in maritime transportation. This study contributes to the advancement of maritime education by reinforcing the importance of sustainability in transportation management and offering a framework for enhancing vocational training in the maritime sector.